2015
DOI: 10.1016/j.juro.2014.11.095
|View full text |Cite
|
Sign up to set email alerts
|

National Practice Patterns of Treatment of Erectile Dysfunction with Penile Prosthesis Implantation

Abstract: Although specialists and high volume surgeons perform a disproportionate number of implant surgeries, low volume surgeons place most penile prostheses in the United States. Additional research is needed to determine best practices to achieve optimal patient outcomes in penile prosthesis surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 25 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…Urologists may apply for certification by the ABU after completing residency and demonstrating an appropriate level of knowledge and expertise in the management of urological conditions. [5, 6]…”
Section: Methodsmentioning
confidence: 99%
“…Urologists may apply for certification by the ABU after completing residency and demonstrating an appropriate level of knowledge and expertise in the management of urological conditions. [5, 6]…”
Section: Methodsmentioning
confidence: 99%
“…Both of them have their pros and cons, but currently the inflatable penile prosthesis (IPP) is used more often in North America and Europe than the non-inflatable and there is a trend toward the use of the IPP in the Southern hemisphere. Analyzing case log data of penile prosthesis implanted by (re)certified urologists from the American Board of Urology from 2003 to 2012, Oberlin and colleagues observed that the proportion of the IPP compared with malleable prosthesis increased twelvefold over these 10 years [19].…”
Section: Types Of Penile Prosthesismentioning
confidence: 99%
“…This decision should be taken with both the physician and the patient, and is usually based on the urologist's comfort with surgical approach, assessment of body habitus, presence of associated conditions (e.g., Peyronie's disease, spinal cord injury), manual dexterity of the patient, and overall cost. In most industrialized countries, if cost is not a limiting factor (e.g., reimbursement by third parties), the three-piece IPP is considered the "gold standard," accounting for 70% of implants in the United States [19], while 20% are two-piece (Ambicor™) and 10% are semirigid rods. This is because, despite its somewhat more complex insertion as it requires the placement of the two cylinders, the pump and the reservoir into the abdominal cavity, the three-piece implant gives the best rigidity and flaccidity since it fills every part of the corporal bodies, and its bigger capacity reservoir permits a better emptying of the cylinders avoiding erectile tissue deterioration, as witnessed with self-contained or two-piece devices with no reserve fluid volume [20].…”
Section: Patient and Implant Selectionmentioning
confidence: 99%
“…The surgery offers high patient satisfaction and has a low rate of complications, especially in the hands of an experienced surgeon. Yet, urologists who perform fewer than five implants per year are responsible for 75% of the penile prostheses in the United States ( 1 ). In the United Kingdom, 80% of surgeons who perform the procedure only place one or two penile prostheses per year ( 2 ).…”
Section: Introductionmentioning
confidence: 99%